2014
DOI: 10.1016/j.tranon.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between LAPTM4B Gene Polymorphism and Susceptibility of Malignant Melanoma in Chinese Patients

Abstract: Lysosomal-associated protein transmembrane 4 beta (LAPTM4B) is known as an oncogene associated with many human malignant tumors. There are two alleles of the gene, LAPTM4B*1 and LAPTM4B*2. Previous studies have shown that LAPTM4B polymorphism contributes to the risk of many cancers. This case-control study was to investigate the relationship between LAPTM4B gene polymorphism and susceptibility of malignant melanoma. The genotypes of LAPTM4B were determined in 617 control subjects and 220 patients with malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…14 Other studies showed no statistical differences between alleles for nasopharyngeal carcinoma, 29 lung cancer, 31 breast cancer, 30 rectal or esophageal cancers, 28 melanoma, 35 and pancreatic cancer. 36 A meta-analysis conducted by Xia et al 37 showed that LAPTM4B polymorphism is associated with an increased risk of cancer in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 97%
“…14 Other studies showed no statistical differences between alleles for nasopharyngeal carcinoma, 29 lung cancer, 31 breast cancer, 30 rectal or esophageal cancers, 28 melanoma, 35 and pancreatic cancer. 36 A meta-analysis conducted by Xia et al 37 showed that LAPTM4B polymorphism is associated with an increased risk of cancer in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that LAPTM4B polymorphisms were related to susceptibility to HCC, 18, 19 breast cancer, 20, 21, 22 non-small lung cancer, 23 gastric cancer, 24 cervical cancer, 25 endometrial carcinoma, 26 colorectal cancer, 27 lymphoma, 28 gallbladder carcinoma, 29 ovarian carcinoma 30 and malignant melanoma, 31 but not to squamous cell carcinomas such as esophageal carcinoma, rectum carcinoma 27 and nasopharyngeal carcinoma. 32 Lately, a meta-analysis in Chinese Han population revealed that LAPTM4B allele *2 carriers exhibited a higher cancer risk compared with allele *1 homozygotes (for *1/2, odds ratio= 1.55, 95% confidence interval 1.367–1.758; for *2/2, odds ratio=2.093, 95% confidence interval 1.666–2.629; for *1/2 + *2/2, odds ratio=1.806, 95% confidence interval 1.527–2.137).…”
Section: Laptm4b Polymorphism and Its Importance In Susceptibility Tomentioning
confidence: 99%
“…Allele *1 contains only one copy of a 19-bp sequence at the 5'UTR in the first exon, whereas the sequence in allele *2 is duplicated and tandemly repeated [14]. Previous study showed that LAPTM4B *2/2-type allele was significantly associated with the susceptibility of various adenocarcinoma including breast cancer [15][16][17], HCC [18,19], non-small lung cancer [20], gastric cancer [21], cervical cancer [22], colorectal cancer [23], lymphoma [24], gallbladder carcinoma [25], ovarian carcinoma [26] and malignant melanoma [27]. Therefore, we hypothesized that if there are some specific transcription factors binding to the LAPTM4B polymorphism region which play important roles in regulating LAPTM4B expression.…”
Section: Introductionmentioning
confidence: 99%